2002
DOI: 10.1038/sj.ijir.3900930
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of penile prosthesis in a patient with severe corporeal fibrosis induced by cavernosal injection therapy

Abstract: Implantation of a penile prosthesis in men with complicated fibrosis of corpus cavernosum is very difficult and even impossible. Cavernosal dilation requires sharp intracavernosal dissection to implant prosthesis, however complete removal of the fibrotic tissue is often impossible. We introduce a new technique using electric resection and electrovaporization of fibrotic tissue for implantation of penile prosthesis in a patient with severe corporeal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Corporal fibrosis and the resultant loss of penile length have stimulated considerable interest in prosthetic urology research. Park and colleagues reported electric resection and electrovaporization of fibrotic tissue for implantation of penile prosthesis in a patient with severe corporeal fibrosis [10]. Mulcahy reported long-term experience with salvage of infected penile implant by the salvage protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Corporal fibrosis and the resultant loss of penile length have stimulated considerable interest in prosthetic urology research. Park and colleagues reported electric resection and electrovaporization of fibrotic tissue for implantation of penile prosthesis in a patient with severe corporeal fibrosis [10]. Mulcahy reported long-term experience with salvage of infected penile implant by the salvage protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral longitudinal corporotomies were made at the penoscrotal junction of the tunica albuginea and extended to the glans penis. The extensive corporeal fibrotic tissue was dissected from the tunica albuginea with scissors and the remaining fibrotic tissue was resected and evaporated with the resectoscope and the resection loop commonly used for transurethral resection [6].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatives have been proposed, all of which involve one or more of the aforementioned reasons for unfavorable outcome [3][4][5][6][7][8][9][10][11].…”
Section: Implantation Of a Penile Prosthesis Into Fibrosed Corpora Camentioning
confidence: 99%
“…Park et al [22] described the use of electrical resection and evaporization utilizing the surgical unit for transurethral resection for excavation of the fibrous tissue in the corpora. This surgery was also performed through an extended corporotomy, which may potentially predispose to prosthesis infection and add to the operation time and effort.…”
mentioning
confidence: 99%
“…[9,12,21,22] Therefore, we think that the ideal surgical technique that can be used in patients with severe corporeal fibrosis to excavate the fibrosed corpora cavernosa for penile prosthesis implantation should be safe, easy, fast, and effective. To the best of our knowledge, the recent study represents the first reported use of a microdebrider in patients with severe corporeal fibrosis to excavate the corpora for penile prosthesis implantation.…”
mentioning
confidence: 99%